The galactic population of low- and intermediate-Mass X-ray binaries - Pfahl, E; Rappaport, S; Podsiadlowski, P (American Astronomical Society, 2003)
We present the first study that combines binary population synthesis in the Galactic disk and detailed evolutionary calculations of low- and intermediate-mass X-ray binaries (L/IMXBs). Our approach allows us to follow completely the formation of incipient L/IMXBs and their evolution through the mass-transfer phase to the point when they become binary millisecond pulsars (BMPs). We show that the formation probability of IMXBs with initial donor masses of 1.5-4 M☉ is typically gsim5 times higher than that of standard LMXBs with initial donor masses of less than 1.5 M☉. Since IMXBs evolve to resemble observed LMXBs, we suggest that the majority of the observed systems may have descended from IMXBs. Distributions at the current epoch of the orbital periods, donor masses, and mass accretion rates of L/IMXBs have been computed, as have orbital-period distributions of BMPs. This is a major step forward over previous theoretical population studies of L/IMXBs that utilized only crude representations of the binary evolution through the X-ray phase. Several significant discrepancies between the theoretical and observed distributions are discussed. We find that the total number of luminous (LX > 1036 ergs s-1) X-ray sources at the current epoch and the period distribution of BMPs are very sensitive to the parameters in the analytic formula describing the common-envelope phase that precedes the formation of the neutron star. The orbital-period distribution of observed BMPs strongly favors cases in which the common envelope is more easily ejected. However, this leads to an approximately hundred-fold overproduction of the theoretical number of luminous X-ray sources relative to the total observed number of LMXBs. As noted by several groups prior to our study, X-ray irradiation of the donor star may result in a dramatic reduction in the X-ray active lifetime of L/IMXBs, and we suggest that irradiation may resolve the overproduction problem as well as the long-standing BMP/LMXB birthrate problem.